Thermal analysis, construction, and monitoring methods for frozen ground - Esch, David C. (American Society of Civil Engineers, 2004)
Thermal Analysis, Construction, and Monitoring Methods for Frozen Ground presents the latest in design theory and engineering practice for analyzing, constructing, and monitoring foundation soils affected by permafrost soils; controlling frost heave of soils; and using artificial freezing methods for stabilizing soft or wet soils to permit excavation for foundations. The design methods, views, and practices of 20 experts in the field of frozen ground engineering are represented in this book. Geotechnical engineers involved in cold region engineering or in the use of freezing techniques to stabilize soils, as well as other any engineers or scientists interested in the prediction of heat transfer in soils will benefit from this publication. Topics include: Ground temperature and temperature observations; Active and passive ground freezing and thawing techniques; Soil thermal properties and analytical prediction methods; Special construction methods and case histories; and Climate change forecasts and trends.